2020
DOI: 10.31031/ntnf.2020.04.000596
|View full text |Cite
|
Sign up to set email alerts
|

Consumers Knowledge About Health Effects of Edible Oils and Fats in Turkey: A Questionnaire Study

Abstract: The aim of this study is to identify the predictors of edible oil and fat consumption. A questionnaire to evaluate the attitude of consumers toward various edible oils and fats was administered to 300 individuals in Manisa. Twenty six percent of participants reported olive oil is the healthiest edible oil. Most of the participants believed that consumption of oils does not lead to health risk if it is not consumed too much. Margarine was reported as the most cholesterol containing item. Fats were associated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Also, all fatty acid profile of the most of common consumed sunflower oil are in the standard rang. Similarly, other studies reported that sunflower is the most consumed oils for cooking in India and Turkey (26)(27) . Compare with the other oils, refined sunflower oil is one of the healthiest and cheapest oils.…”
Section: Discussionmentioning
confidence: 63%
“…Also, all fatty acid profile of the most of common consumed sunflower oil are in the standard rang. Similarly, other studies reported that sunflower is the most consumed oils for cooking in India and Turkey (26)(27) . Compare with the other oils, refined sunflower oil is one of the healthiest and cheapest oils.…”
Section: Discussionmentioning
confidence: 63%
“…The previous studies reported that the saturated oils are oxidized less quickly than unsaturated oils; the relative auto-oxidation rate of PUFAs, oleic (18:1 Δ9c), linoleic (18:2 Δ9c, 12c), and linolenic acids (18:3 Δ9c, 12c, 15c), are 1:40 to 50:100 on the basis of oxygen uptake, and 1:12:25 on the basis of peroxide formation. Thus, the distribution of FAs in vegetable oils is very important for consumers in terms of diet and health (Orsavova et al, 2015;Özbek et al, 2020). Health professionals recommend diets with low energy, low cholesterol, low SFA, and a good n6/n3 ratio to decrease heart disease and others (Briggs et al, 2017).…”
Section: Fatty Acid Composition (Fac)mentioning
confidence: 99%
“…(Ali and Kapoor, 2010) Diet and lifestyle can be modified in order to prevent these type of noncommunicable diseases and this area has been the main focus of nutrition based research. In order to overcome this common complication, general public should have adequate and accurate knowledge and awareness about what they consume as food (Aksoylu Özbek, Çelik and Günç Ergönül, 2020). At the same time, there are numerous spook stories about different fats and oil varieties.…”
Section: Introductionmentioning
confidence: 99%